Recipe for disaster - Benton, Jim (Benton, Jim. Franny K. Stein, mad scientist, 2020)
Concerned that the fundraisers for the school art and music departments are not doing well, Franny K. Stein creates in her laboratory/kitchen an irresistible muffin recipe.